PROFESIONALISME DAN KUALITAS PENGELOLAAN SUMBER DAYA MANUSIA PADA PROGRAM PAUD(STUDI KASUS DI KOBER MELATI PUTIHKECAMATAN UJUNGBERUNG, KOTA BANDUNG) - Wawan Hermawan; Eli Endrawati; Eva Bella Nuarida (Jurnal Intelek Insan Cendikia, 2025)
Pendidikan Anak Usia Dini (PAUD) is a coaching effort aimed at children from birth to the age of six years which is done through the provision of educational stimuli to help the growth and development of physical and spiritual so that children have readiness to enter further education. Professionalism in the management of human resources in early childhood education institutions is not only related to the teaching skills possessed by educators, but also to the way institutions manage and develop human resources in a systematic and structured manner. Professionalism includes aspects of competence, work ethics, and adequate attitudes in carrying out their duties as educators and managers of early childhood education. Professional educators are able to adjust to the development of children, using appropriate methods, and constantly improve their capacity through training and career development this study aims to analyze the professionalism and quality of Human Resource Management in Pendidikan Anak Usia Dini (PAUD) in Kober Melati Putih, Ujungberung District, Bandung. The main focus of this study is to examine how the level of professionalism of educators and Human Resource Management affect the effectiveness of the implementation of early childhood education programs. The research method used is a case study with a qualitative approach. Data was collected through observation, in-depth interviews, and documentation studies to obtain a comprehensive picture of human resource management practices in the institution. The results showed that the professionalism of educators in Kober Melati Putih is reflected in the commitment to the task, adequate pedagogic skills, as well as the ability to build positive relationships with children and parents. In addition, the quality of Human Resource Management is supported by a structured system of recruitment, training, and performance evaluation. Nevertheless, the study also found some challenges, such as limited ongoing training facilities and lack of adequate financial support. Therefore, efforts are needed to improve professionalism through regular training and strengthening of management systems to ensure a more optimal quality of educational services.